The effect of leverage, profitability, and profit growth on earnings quality - Pangesti, Mutiara Dian; Sugiarti, Sugiarti; Siddiq, Faiz Rahman (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2023)
Earnings quality is the quality of earnings information which can show how much influence earnings have on decision making and can assist investors in evaluating company performance. This study aims to analyze the effect of leverage, profitability, and profit growth on earnings quality. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period, totaling 213 companies. The sample in this study was obtained using a purposive sampling method, in order to obtain a sample of 370 samples from 74 companies during 5 years of observation. This study uses data obtained from the annual financial reports of manufacturing companies. The data analysis technique used in this study is multiple linear regression analysis using IBM SPSS 21 software. The results of this study indicate that leverage has no effect on earnings quality. While profitability and profit growth have a positive effect on earnings quality.